Mechanism to detect windows of opportunities for implementing new technical and technological solutions for the purpose of industrial organizations sustainable development - L. S. Zelentsova; M. V. Spesivtseva (Вестник университета)
The article considers the problem of identifying windows of opportunity for the sustainable development of the Russian industrial sector. The relevance of this article is due to the need to improve the mechanism of communication between the innovative and practical environments of the domestic industry, to identify the optimal terms and conditions for the implementation of new technical and technological solutions. Based on the analysis of the factors affecting the prospects for the practical implementation of innovations, it is shown that changing over time, they at certain times create technological windows of opportunity for enterprises with the most favorable combination of needs, readiness and capabilities of an economic entity to use the innovations proposed by developers. Their timely identification will help to improve targeting and reduce the timing of innovation. The article presents concept map of the formation of a mechanism for identifying windows of opportunity, which provides for its decomposition into three consecutive hierarchical levels – the level of analysis of influencing indicators, the level of identification of compliance of the innovation with the needs of the enterprise and its capabilities. The purpose of this work is to determine approaches to the creation of a preventive assessment mechanism and to establish the most favorable combinations of factors of technical and technological development of industrial organizations in the most appropriate, but critically short time.